A Comprehensive Analysis On Efficient Multimedia Storage Mechanism In Public Cloud Environment With Secured Access (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Dynamic on-demand service has become the crucial part in cloud computing according to the user’s requirements. Cloud storage is clearly the top choice for archiving media assets, by choosing the public cloud for active, deep archive needs. Video on demand, media distribution system in cloud allowing users to access video, facilitating immediate download and view of data without traditional video playback devices. On demand service of video requires infrastructure resources to handle large load fluctuations. Major challenges of video demand services are delays in simultaneous video uploading, processing, accessing and traffic caused by exhaust services. Also, there are concerns over the security of assets stored in a public cloud remains. In this paper, an ample analysis is presented on file storage encompassing fragmentation, compression, encryption security concerns in cloud storage and access. The limitations in the existing is also provided and hence outlined the research direction towards an efficient storage mechanism with a secured access providing a reliable media data transmission between data owner and users in public cloud environment.